Molecular ecology of Long-finned pilot whales (Globicephala melas) in the eastern North Atlantic - Ball, Rachel (University of Chester, 2023)
The long-finned pilot whale (LFPW) (Globicephala melas) is a large matrilineal odontocete, has antitropical distribution, with a subspecies in each Hemisphere, G. melas melas in the North Atlantic, and G. melas edwardii throughout the Southern Hemisphere. It is the species most commonly encountered in mass stranding events (MSE) globally. The causes driving such events are often complex and multi-layered or even indeterminable. However, social cohesion or the disruption of the species’ renowned social bonds are thought to be a key factor, regardless of other external influences. This PhD thesis aimed to explore this by employing mtDNA and nuclear genetic markers to investigate kinship among samples collected from MSE and an “at-sea” pod group. Six MSE were analysed with a panel of microsatellite markers to determine the kinship dyads within each event. In all but one MSE calves were found with missing mothers, and in some events mother-offspring dyads were separated over different stranding phases, suggesting that disruption of these important relationships can cause/extend MSE. Additionally, samples from a grind (caught pod) were included in analysis to compare an “at-sea” pod assemblage to those involved in a MSE. Confirming that LFPW pods are composed of highly related small family groups, a pod unit, these pod units are found in association with other such units, a pod complex and this is conserved across both individuals “at-sea” and those within a MSE. This also indicates that MSE may not be driven by kin group disruption per se. Population structure across the eastern North Atlantic was also assessed using a combination of mtDNA, microsatellites, and RAD-Seq. Although, mtDNA reported significant differentiation between Scotland and Ireland, the nuclear data supported a lack of neutral and non-neutral genetic structure. This demonstrates the weakness of using only mtDNA to infer population structure within a species with matrilineal groups, while the high population connectivity is important in terms of ...